2023
DOI: 10.1038/s41522-023-00457-6
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the infant male urobiome and genomic analysis of Actinotignum spp.

Seth A. Reasoner,
Viktor Flores,
Gerald Van Horn
et al.

Abstract: The urinary bladder harbors a community of microbes termed the urobiome, which remains understudied. In this study, we present the urobiome of healthy infant males from samples collected by transurethral catheterization. Using a combination of enhanced culture and amplicon sequencing, we identify several common bacterial genera that can be further investigated for their effects on urinary health across the lifespan. Many genera were shared between all samples suggesting a consistent urobiome composition among … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 89 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…However, EQUC and culture-independent 16S sequencing do not always reconcile. For example, the families detected most frequently by EQUC by Reasoner et al ( 21 ) were not detected in culture-independent sequencing results at all, and several families detected most frequently by 16S sequencing were not detected in EQUC isolates. 16S sequencing methods are limited by available mapping to known genetic sequences in available databases, and EQUC still is not a fully comprehensive method of culturing all species.…”
Section: Methods Employed In Pediatric Urobiome Studiesmentioning
confidence: 94%
See 4 more Smart Citations
“…However, EQUC and culture-independent 16S sequencing do not always reconcile. For example, the families detected most frequently by EQUC by Reasoner et al ( 21 ) were not detected in culture-independent sequencing results at all, and several families detected most frequently by 16S sequencing were not detected in EQUC isolates. 16S sequencing methods are limited by available mapping to known genetic sequences in available databases, and EQUC still is not a fully comprehensive method of culturing all species.…”
Section: Methods Employed In Pediatric Urobiome Studiesmentioning
confidence: 94%
“…Swabs of adjacent niches had similar results (>90%). Reasoner et al ( 21 ) modified the EQUC protocol and with its use, identified growth in 65% of urine samples in at least one growth condition. They were also able to detect additional families and species in their samples using MALDI-TOF.…”
Section: Methods Employed In Pediatric Urobiome Studiesmentioning
confidence: 99%
See 3 more Smart Citations